The drum : a history - Dean, Matt, 1980- (Scarecrow Press, 2012)
The Drum: A History highlights the different uses and customs associated with drumming and examines how the drum developed across many cultures and over thousands of years before they became the instruments we know today. Bringing its history to the pre.